Presleep focusing on positive spontaneous thoughts enhanced the possibility of dreaming of them - Wang, Jiaxi; Song, Bin; Feng, Xiaoling; Shen, Heyong; Liu, Ruoqiao (Frontiers in Psychology, 2022)
Introduction Dreaming is the subjective experience during sleep. A spontaneous thought is a thought that comes to one’s mind involuntarily. This study investigated whether presleep focusing on a positive spontaneous thought enhanced the possibility of dreaming of the thought. Methods Ninety-seven participants were quasi-randomly assigned to an expression condition (focus on an spontaneous thought for 5-Min before sleeping; N = 45) and a control condition (think about anything for 5-Min before sleeping; N = 45). Participants completed a dream diary upon waking. Then, both participants themselves (the selfrating method) and external judges (the external-rating method) rated the correlation between the positive spontaneous thought and the dream. Results The result of the external-rating method indicated that presleep focusing on positive spontaneous thoughts enhanced the possibility of dreaming of the thoughts. In addition, the external-rating method found that presleep focusing on positive spontaneous thoughts enhanced the possibility of dreaming of thoughts that were related to the positive spontaneous thoughts but not the positive spontaneous thoughts themselves. Discussion These results supported the current concern theory which suggests that one’s current concerns increase responses to cues related to the concerns implicitly. In addition, these results supported the continuity hypothesis which states that dreaming is in continuous with waking life, and thus the intensity of a daily concern may be related to the possibility of dreaming of the daily concern.